A revision of the genus Disparalona (Cladocera, Chydorinae) in South America - Sousa, Francisco Diogo R.; Elmoor-Loureiro, Lourdes M.A.; Mugnai, Riccardo; Panarelli, Eliana Aparecida; Paggi, Juan César (European Journal of Taxonomy, 2018)
The genus Disparalona Fryer, 1968 comprises a well-defined species complex, the hamata-group, which might have sibling species in South America. This hamata-group needs urgent revision. Besides that, a complete morphological evaluation of the endemic species D. leptorhyncha (Daday, 1905) is lacking. Thus, the aim of the present study is to revise populations of species of the hamata-group in South America and to redescribe D. leptorhyncha. Our findings pointed to an occurrence of species which are part of the Disparalona (Mixopleuroxus) linage. Currently, the Neotropics have the highest diversity to the genus, with three species of the hamata-complex – D. (M.) hamata (Birge, 1879), D. (M.) lucianae sp. nov., D. (M.) tenuispina sp. nov. – in addition to D. (M.) leptorhyncha. These species can be differentiated from each other by the morphology of their rostrum, labrum, and postabdomen.